Nepenthes alzapan (Nepenthaceae), a new species from Luzon, Philippines - Cheek, Martin; Jebb, Matthew (Phytotaxa, 2013)
This paper forms a part of the studies towards a World Monograph of Nepenthes Linnaeus (1753: 955) building on a Skeletal Revision of Nepenthes (Jebb & Cheek 1997) and the Flora Malesiana account (Cheek & Jebb 2001). In the course of studying previously unseen specimens from the Philippines, four sheets (Ramos & Edanõ 45690, K, NY, UC, US), of a species previously unknown came to light from Mt Alzapan. The oblong, glabrous, ligulate, sessile leaf-blades with 5–7 pairs of nearly evenly spaced longitudinal nerves placed the species unambiguously in the Insignes group of Danser (1928) which is restricted to the Philippines apart from one species, N. insignis Danser (1928: 314), in New Guinea and, more ambiguously, N. northiana Hooker, J.D. (1881: 717) in Borneo (Cheek & Jebb 2001).